PENGARUH LEMBAR KERJA SISWA TERINTEGRASI MATERI ENERGI PANAS BUMI TERHADAP PENCAPAIAN KOMPETENSI FISIKA SISWA DI SMA - Ratna Mila; Ahmad Fauzi; Syafriani . (Universitas Negeri Padang, 2018)
ABSTRACTLow achievement of students competence are caused by lack of motivation for problem solving abilities of students. Problem-solving abilities on competence of knowledge is least students who are able to answer questions above the level of C3(aplication). Competence of skill is only some students who are able to problem solving with scientifi and have difficulties in solving the existing problems on teaching of student worksheet, that affecting achievement of student competence. Student motivation in problem solving can be enhanced by learning that is contextual, authentic and close to student life that is by integrating real problem and emerging issue into student learning process. Environmental problems faced by human is the limitation of energy in fulfilling their needs, while the province of West Sumatra is one of the provinces that have the potential of geothermal energy source because it is on the path of the volcano that should be developed and educate students in energy savings. The LKS is designed to integrate geothermal energy materials using the Reasoning and Problem Solving learning model. The purpose of the study, to investigate whether there is influence and how much contribution integrated geothermal energy LKS to the achievement of student competence. The type of research is quasi experiment and randomized control group design design that the study population is X class MIA students registered in the even semester of academic year 2016/2017. The sample was taken by purposive sampling technique. The research instrument is the final test to measure knowledge competence, observation sheet, self-assessment, and peer assessment to measure attitude competence, skill competency appraisal sheet to measure skill competence, and LKS assessment sheet. The data analysis used two-point equality test, linear regression test, and correlation test.Based on the data analysis, the students' knowledge, attitude and skill in the experimental class were 89.96; 84.85; 87.21 and control classes respectively 84.96; 82.98; 82,71. From t test, obtained t count> ttable so that null hypothesis rejected and alternative hypothesis accepted. With correlation test, the contribution of geothermal energy integrated LKS is 36,40% in knowledge competence, 33,64% on attitude competence, and 54,78% on skill competence. Based on the result, it can be concluded that there is influence and contribution of integrated LKS geothermal energy material to the achievement of students' competence to real level 0,05 on temperature material, calorie and optics in class X SMAN 12 Sijunjung..